The Power of the Written Word in Manichaeism - Moiseeva, Evgenia (Numen, 2022)
The prominent role books and the act of writing played in the life of the Manichaean Church distinguishes Manichaeism even among other “religions of the book.” This article tackles the question whether the primacy of writing was established by Mani himself or resulted from a development that occurred within the first generations of Mani’s followers. The analysis of the extant fragments of Mani’s own works and early Manichaean texts such as the work of Baraies preserved in the Cologne Mani Codex and the Kephalaia indicate that Mani’s superiority as a writing prophet and the ritual meaning of writing most likely were not part of Mani’s original teaching. Rather, they resulted from the efforts of Manichaean theologians who sought to demonstrate the exceptional status of Mani’s revelation and prophetic mission based on his writings. The Prologue to the Kephalaia of the Teacher played a significant role in this development and contributed extensively to the ritualization of writing in Manichaeism.